OPTIMIZATION, ASSIGNMENT MODEL, AND DECISION ANALYSIS OF HOSPITAL CALL CENTER IN PT. XYZ - I Nyoman Indra Kusuma Sukma Putra; Aryo Robinsar Simanjuntak; Angeliliana Surya; Desnita Putri Ardiyanti; Christy Dwita Mariana2 (Jurnal Ekonomi, 2022)
The acquisition led PT XYZ management to prioritize improving the hospital’s public service. One of the main focuses is the centralization of the Call Center from 6 Hospital branches in several areas of Greater Jakarta.  The Call Center centralization plan also need to conduct several analysis using Optimization Model, Assignment Model, and Decision Analysis to increase operating staff's effective performance and to make sure the management decision is aligned with the Hospital’s management plan.